Fucoxanthin Attenuates Hydrogen Peroxide-induced Oxidative Stress in Placenta-derived Mesenchymal Stem Cells through Antioxidant Activity - Suwanmanee, Gunticha; Tantrawatpan, Chairat; Kheolamai, Pakpoom; Tantikanlayaporn, Duangrat; Manochantr, Sirikul (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Osteoporosis is a bone disease that results in a loss of bone mass. Oxidative stress promotes osteoblast apoptosis which leads to decrease bone formation. Fucoxanthin, a carotenoid extracted from brown seaweeds, has antioxidant activity through an increased antioxidant enzyme expression. Objectives: This study attempts to explore the cytoprotective effect and antioxidant activity of fucoxanthin to promote the cell viability of placenta-derived mesenchymal stem cells (PL-MSCs) under oxidative stress conditions. Methods: PL-MSCs were obtained from a pregnant woman after normal delivery. Following the characterization, PL-MSCs were treated with fucoxanthin (1-5 µM) and 750 µM H2 O2 for 24 h or cultured in both fucoxanthin (1-5 µM) and H2 O2 for 24 h. The cell viability, intracellular reactive oxygen species(ROS) production,superoxide dismutase (SOD) activity and glutathione (GSH) were determined following treatment. Results: The resultsshowed that treatment and pretreatment with fucoxanthin increased cell viability, SOD activity, GSH levels of PL-MSCs when compare to control which cultured in 750 µM H2 O2 without fucoxanthin for 24 h. While, treatment and pretreatment with fucoxanthin decreased intracellular ROS production of PL-MSCs when compare to control which cultured in 750 µM H2 O2 without fucoxanthin for 24 hours. Conclusions: This study demonstrated that the treatment and pretreatment with fucoxanthin increased the viability and increased antioxidant activity of PL-MSCs when compared with the control which cultured in 750 µM H2 O2 without fucoxanthin. In addition, the treatment with fucoxanthin decreased intracellular ROS production compared with the control. This study established that fucoxanthin can protect PL-MSCs against oxidative stress.